2007
DOI: 10.1063/1.2753715
|View full text |Cite
|
Sign up to set email alerts
|

Absence of long-range Ni∕Mn ordering in ferromagnetic La2NiMnO6 thin films

Abstract: Epitaxial La 2 NiMnO 6 thin films have been grown on (001)-orientated SrTiO 3 using the pulsed laser deposition technique. The thin films samples are semiconducting and ferromagnetic with a Curie temperature close to 270 K, a coercive field of 920 Oe, and a saturation magnetization of 5 µ B per formula unit. Transmission electron microscopy, conducted at room temperature, reveals a majority phase having "I-centered" structure with a ≈ c ≈ a sub 2 and b ≈ 2a sub along with minority phase domains having a "P-typ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
122
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(132 citation statements)
references
References 14 publications
7
122
1
Order By: Relevance
“…It is here important to note these three distinct phases are thermodynamical stable. Also of importance, the short-range ordering can also be induced through oxygen or cation vacancy and thus is very sensitive to the synthesis conditions 5,10 . This outlines the real complexity associated in obtaining a totally ordered phase.…”
Section: B'/b'' Cation Ordering: a General Perspectivementioning
confidence: 99%
“…It is here important to note these three distinct phases are thermodynamical stable. Also of importance, the short-range ordering can also be induced through oxygen or cation vacancy and thus is very sensitive to the synthesis conditions 5,10 . This outlines the real complexity associated in obtaining a totally ordered phase.…”
Section: B'/b'' Cation Ordering: a General Perspectivementioning
confidence: 99%
“…The arrangement of transition metal ions in oxide magnetic materials plays a crucial role on its structure as well as on physical properties [1][2][3]. In particular the arrangement of transition metal ions in tetrahedral and/or octahedral sites of spinel structure is very appealing.…”
mentioning
confidence: 99%
“…For LNAMO, it is about 3.99 Å. Surprisingly, these artificial oxides show a significant enhancement in their pseudo-cubic lattice parameter compared to their respective LCMO (~ 3.89 Å) and LNMO (~ 3.87 Å) bulk and thin films [6][7][8][9][10][11][12][13][14] . We interpret this counter-intuitive behaviour as an indication that the presence of Al in the crystal structure provokes an expansion of the out-of-plane lattice parameter to minimize the elastic and columbic energy of these polar systems.…”
mentioning
confidence: 99%
“…In our recent studies of self-ordered La 2 CoMnO 6 (LCMO) thin films grown by pulsed-laser deposition, we demonstrated that the ordered Co/Mn cations can be obtained only in a limited window of growth parameters 11 . It has been clearly established that the magnetic behaviour of these compounds is a very sensitive probe of the presence of cation ordering [5][6][7][8][9][10][11][12][13][14] . Furthermore, the MnO 6 and CoO 6 layers with Mn 4+ and Co 2+ ions alternating along the (111) crystal axis generate a strong polar character as confirmed by an enhanced dielectric constant 14 and a large magnetodielectric coupling in the vicinity of the magnetic phase transition 7,[14][15] .…”
mentioning
confidence: 99%
See 1 more Smart Citation